Efficient removals of Hg and Cd in aqueous solution through NaOH-modified activated carbon fiber - Kim, Doo-Won; Wee, Jae-Hyung; Yang, Cheol-Min; Yang, Kap Seung (ELSEVIER SCIENCE SA, 2020)
This manuscript describes an efficient and cost-effective method to remove heavy metals of Hg and Cd in aqueous solutions via adsorption on activated carbon fibers after modification with NaOH solution (NaACF). The Hg and Cd metals in the aqueous solution exist as Hg(OH)(2) and Cd2+ in the experimental condition of pH 6-8. Surface characterization of the NaACF reveals uniform and narrower micropores with an increase in oxygen functional groups of phenol and lactone compared with the original ACF (pACF). The NaACF demonstrates a superior adsorption rate to both aqueous samples of heavy metal compounds. The granular activated carbon (GAC) with diverse pore structures consisting of micropores, mesopores, and macropores adsorbed the heavy metals at a relatively slow rate. The adsorption mechanisms of the heavy metals into NaACF pores are proposed as pore-filling with non-ionic Hg(OH)(2) and electron sharing of oxygens in phenolic, lactone, and carboxylic acid groups with ionic Cd2+. The results from continuous feeding are also reported for the sample blend of 10 wt% NaACF and 90 wt% GAC in increasing the cost performance ratio.
Keywords: HEAVY-METAL IONS; WATER-TREATMENT; ADSORPTION; ACID; CADMIUM; CD(II)